The influence of Delirium in the time of mechanical ventilation in critical patients: a systematic review - Krebs, Jessica Aline; Osaku, Erica Fernanda; Costa, Claudia Rejane Lima de Macedo; Ogasawara, Suely Mariko; Costa, Jaquilene Barreto da; Taba, Sheila; Jorge, Amaury Cezar; Duarte, Pericles Almeida Delfino (ABCS Health Sciences, 2018)
Delirium consists of an acute, fluctuating, confusional state, representing a manifestation of cerebral dysfunction that can occur with different clinical manifestations. Patients with delirium have been studied because they have had longer time of mechanical ventilation and hospitalization in the intensive care unit. The objective of the study was to perform a literature review about the influence of delirium on the time of mechanical ventilation, sedation and on the mortality of patients admitted in intensive care units. A search for studies with the keywords delirium, intensive care unit and mechanical ventilation was performed in PubMed and Embase databases. As result eight articles were included, one received level A and seven received level B on the Oxford scale. The main results were: Patients with delirium presented greater severity, longer time of mechanical ventilation, longer sedation time and higher mortality. It is concluded that delirium appears to be associated with longer mechanical ventilation, greater sedation and mortality rates in these patients.